Penguatan Literasi Keagamaan Perempuan Melalui Pelatihan Tafsir - Zulaika, Zulaika; Syafira Azzahra, Siti; Vahlepi, Sahrizal (Al-Khidmah Jurnal Pengabdian Masyarakat, 2025)
This community engagement program aims to enhance women’s religious literacy through a thematic Qur’anic interpretation training using the Participatory Action Research (PAR) approach within the BKMT community of Telanaipura District, Jambi City. The program focuses on strengthening women’s contextual understanding of Islamic teachings by involving 25 active female members of the majelis taklim in six training sessions conducted at Nurul Iman Mosque and participants’ homes. The core themes included women’s roles in the Qur’an, gender justice, Qur’anic family values, and religious moderation. The PAR approach was implemented through stages of coordination, needs assessment, thematic module development, interactive training, reflection, and evaluation. Qualitative data were collected through observation, group discussions, and participant reflections, then descriptively analyzed to capture learning dynamics and knowledge transformation. The results revealed a significant improvement in participants’ ability to interpret Qur’anic verses contextually, accompanied by increased awareness of moderation, justice, and equality in religious life. Participants showed active engagement and initiated independent women’s Qur’anic study groups as a follow-up action. This training demonstrates that participatory learning effectively empowers women through religious literacy by enhancing not only spiritual understanding but also leadership, solidarity, and social responsibility. The practical implication suggests that the PAR-based thematic tafsir training model can be replicated in other majelis taklim communities to foster a moderate, inclusive, and just Islamic society.